THE IMPACT ON TRUST AND ONLINE BUYING DECISIONS THROUGH INFORMATION QUALITY, CELEBRITY ENDORSER AND PRICE PERCEPTION AT INSTAGRAMS IN SURABAYA - Halik, Abdul (Archives of Business Research, 2020)
the development of e-commerce today is not only selling and buying products online but also people are always using the internet for convenience in their lives. Activities in e-commerce include the process of providing products, sales, services, shipping and payment systems for consumers with the support of a network of business partners throughout the world. The internet for business people can be used to market products with low advertising costs. Instagram is one of the internet sites in Indonesia that implements the e-commerce system in the world. This website, Instagram, is visited by many people from Indonesia and abroad because it is easy to access. Instagram provides a business profile account that has its advantages for business people. Instagram is a social media based on mobile applications, so it is easy to use wherever you want to access your account without using a computer. Using the Instagram application there are no special requirements for selling or shopping on the Instagram application, but you need to register an account on Instagram, then you can take advantage of all the features offered by this application. The aim of making it easier to buy and sell people online and get efficiency in online shopping. The research objective is to find out the significances of trust, celebrity endorser, and price perception on online purchasing decisions via Instagram. There are 200 online respondents in Surabaya to get these data. This type of research is a quantitative research method with an explanatory method to get the answers. Each variable can be known to contribute to shaping consumers to make online buying decisions. The tool used to analyze this research is SEM version of AMOS 24. Research with information quality, celebrity endorser and price perception influences trust as an intervening variable of purchasing decisions. These mean the exogenous variables used in this study affect consumer confidence. The information presented is clear, the role of the maximum endorser and the perceived price perception can be trusted, then online shoppers will immediately decide to buy the items needed. While the direct effect of the exogenous variable to the endogenous variable is only the price perception variable which has a positive and significant effect. The information quality and celebrity endorsers have a positive but not significant effect, meaning that consumers who buy only see offers of prices related to discounts, free shipping, and guarantees provided by online sellers. The information quality in the online purchasing process makes consumers adequate trusted the information that is displayed on Instagram. The role of celebrity endorsers in advertising products or services is desirable to motivate prospective online buyers. The endorsers can increase the enthusiasm to buy items that are promoted on Instagram. It can influence consumers buying decisions. Moreover, confidence variables can help remind consumers of complete information, famous endorsers and price perceptions that include price discounts, guarantees on products purchased until they are in good condition and according to buyer expectations. Online businesses must take all risks because there is no guarantee that the products received are the same as the picture displayed. Information that is easily accessible and discounted prices that are interested and gives reasonable guarantees to consumers. Trust will grow well if supported by clear information, there will be an online purchasing decision. The existence of an online business can provide convenience to human needs and job creation to reduce unemployment in Indonesia, especially the young generation.